(untitled) (New Collegium, 2020)
University-School clusters: Best practices and the prospects for their adaptation to Ukrainian context : the XVIII International Scientific and Practical Conference (14-th Febuary 2020, Kharkiv Univ. of Humanities “People’s Ukrainian Acad”. The task of determining the place and role of primary school within the framework of the functioning of the scientific and educational cluster is actualized in the work. The main purpose of existence of a scientific and educational cluster, which is the conditions conducive to the formation of an educational institution as a school of experience and development, a space for free decision making, problem solving, manifestation of initiative and development of independence, a school in which the ways of handling knowledge, finding it, its selection, application and endowment with personal meanings are taught; in which there is a formation of a person with a value-based attitude to the process of self-development is revealed. A connection between the research activities of the educational process subjects and the synergistic action of development resources in the educational cluster is established. The research work of younger schoolchildren is considered as an element of the mechanism of interaction within the educational cluster. The scheme of the organization of research work of primary schoolchildren in the scientific and educational cluster, that KSU "NUA" is, consisting of four components is presented: A training system aimed at becoming a subject of educational activity; “Researcher’s Day” – implementation of STEM – STEAM – STREAM – education ideas; “Start into science” – the defense of research papers prepared during the academic year at the scientific-practical conference of primary schoolchildren; “Smart meetings” – meetings with scientists, practitioners, organized at the intellectual request of younger students. It is concluded that the organization of research work of primary schoolchildren within the framework of the functioning of the scientific and educational cluster of NUA provides a unique developing effect for students.